2022
DOI: 10.1001/jamaneurol.2022.3282
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic Lateral Sclerosis Clinical Trials and Interpretation of Functional End Points and Fluid Biomarkers

Abstract: ImportanceClinical trial activity in amyotrophic lateral sclerosis (ALS) is dramatically increasing; as a result, trial modifications have been introduced to improve efficiency, outcome measures have been reassessed, and considerable discussion about the level of data necessary to advance a drug to approval has occurred. This review discusses what recent pivotal studies can teach the community about these topics.ObservationsBy restricting inclusion and exclusion criteria, recent trials have enrolled population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…However, the post hoc analyses showed that the drug slowed the progression of those within 12 months’ duration ( Kaji et al, 2019 ). The criteria that selectively enroll patients with rapid or slow progression rates also increase the homogeneity of the population and thus have a better chance of efficacy being observed ( Shefner et al, 2022 ). Therefore, using more specific inclusion criteria to recruit homogenous patients, especially those with a rapid progression rate, may increase the chance of finding effective drugs, although whether the results can be translated to a more general population remains a concern.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the post hoc analyses showed that the drug slowed the progression of those within 12 months’ duration ( Kaji et al, 2019 ). The criteria that selectively enroll patients with rapid or slow progression rates also increase the homogeneity of the population and thus have a better chance of efficacy being observed ( Shefner et al, 2022 ). Therefore, using more specific inclusion criteria to recruit homogenous patients, especially those with a rapid progression rate, may increase the chance of finding effective drugs, although whether the results can be translated to a more general population remains a concern.…”
Section: Discussionmentioning
confidence: 99%
“…Stringent disease and diagnosis may also influence the rate. However, the short observation period may be remedied by assessing the longer follow-up or use of demographic cofactors ( Shefner et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations